Evaluation and ex situ conservation of indigenous (Naati) mango cultivars - Dinesh, M.R.; Ravishankar, K.V.; Nischita, P.; Sandya, B.S.; Lavanya, B.; Sthapit, B.R. (International Society for Horticultural Science, 2016)
Mango is one of the most important fruit crops, valued commercially for its taste and quality. India is the major centre of diversity as far as Mangifera indica is concerned. Due to rapid industrialization large number of local (Naati) indigenous cultivars is being lost. An attempt was made to collect, evaluate and conserve indigenous types 35 locally on farm in two locations at Chittoor, Andhra Pradesh. The main idea behind conservation in such diversity parks is that these cultivars, which have evolved in a particular place, would be conserved ex situ but in almost similar eco-geographical conditions. Evaluation and molecular characterization carried out showed wide diversity for fruit quality traits. Some of the indigenous genotypes viz., Lalbaba, Chittithotha, and TSAN6 etc. were observed to have good fruit quality traits. Hence, these types have scope for further for use in breeding programme and cultivation.